Geopolitical and Economic Implications of Brexit in the European Union (2020)
The objective of this research article is to analyze the economic and geopolitical implications of Brexit for the European Union and Great Britain. It corresponds to qualitative research with descriptive scope, framed in the interpretive paradigm. Documentary sources were consulted to achieve the objectives, and the information collected was submitted to a coding and categorization process through the Atlas Ti software. The results of the analysis allow us to present the findings in two sections: 1) the causes and process of Brexit, making special reference to the political reasons and the results of the 2016 vote; 2) the impacts of Brexit according to the analysis of the literature, which are codified and categorized for a better understanding of the phenomenon. Although there is an important literature on the many and varied effects of Brexit, only in the next few years can the implications of this phenomenon be recognized for interest groups.